2022
DOI: 10.1108/arj-01-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of XBRL adoption on financial reporting quality: a global evidence

Abstract: Purpose This paper aims to examine the effect of eXtensible Business Reporting Language (XBRL) adoption on financial reporting quality at the country-level (developing and developed countries). Design/methodology/approach This study uses data from 98 developed and developing countries between 2005 and 2018. This study collected data from various sources such as the World Economic Forum, World Development Indicators, World Governance Indicators and XBRL website. Findings The results show that XBRL is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 60 publications
2
15
0
1
Order By: Relevance
“…One possible explanation for this finding is that the effects of XBRL adoption in developed countries may be differ from those in developing countries due to a lower level of institutional quality. This is in line with Tawiah and Borgi (2022) who found that the effect of XBRL adoption on the quality of financial reporting differs between developed and developing countries.…”
Section: Test Of Hypothesissupporting
confidence: 91%
See 1 more Smart Citation
“…One possible explanation for this finding is that the effects of XBRL adoption in developed countries may be differ from those in developing countries due to a lower level of institutional quality. This is in line with Tawiah and Borgi (2022) who found that the effect of XBRL adoption on the quality of financial reporting differs between developed and developing countries.…”
Section: Test Of Hypothesissupporting
confidence: 91%
“…It is currently mandatory in many countries and voluntary in others. In addition, XBRL is constantly progressing, and the number of XBRL-based projects is growing rapidly (Tawiah & Borgi, 2022).…”
Section: Xbrl (Extensible Business Reporting Language) and Taxonomymentioning
confidence: 99%
“…The main theoretical contributions of this paper to technology in financial reporting, XBRL and accounting literature are that it sheds light on the influence of the use of technologies in the business reporting process and their influence on various aspects of business reporting, which has only received confined focus from earlier studies so far (Siano et al, 2018;Bernardi, 2020;Abeywardana et al, 2022;Tawiah and Borgi, 2022). Thus, this study extends the research that examines the role of technology in enhancing the quality of business reporting.…”
Section: Introductionmentioning
confidence: 75%
“…For instance, many earlier studies (Geiger et al, 2014;Mao and Zhang, 2019;Hoitash et al, 2021;Ilias et al, 2020;Cormier et al, 2022) studied the use of XBRL for financial reporting, but their focus was on its functioning, efficiency, taxonomy design, benefits and opportunities. Only a few studies conceptually focused on XBRL and its influence on financial reporting quality (Tarmidi and Roni, 2014;Al-Ramahi et al, 2021;Tawiah and Borgi, 2022). Therefore, the present study is unique among XBRL literature and tries to analyse the influence of XBRL and its functionality on various aspects of financial reporting and its quality at large.…”
Section: Introductionmentioning
confidence: 99%
“…It solves significant challenges such as insufficient physical storage capacity, lengthy procedures, human error, delay and missing physical documentation [Companies Commission of Malaysia (CCM), 2019]. XBRL’s ability to accurately read and transfer the data into electronic communication devices can improve CCM comparability, auditing and monitoring processes (Tawiah and Borgi, 2022; Faccia et al , 2019).…”
Section: Introductionmentioning
confidence: 99%